Chemical characterization of the adhesive secretions of the salamander Plethodon shermani (Caudata, Plethodontidae) - Janek von Byern; Ingo Grunwald; Max Kosok; Ralph A. Saporito; Ursula Dicke; Oliver Wetjen; Karsten Thiel; Kai Borcherding; Thomas Kowalik; Martina Marchetti-Deschmann (Scientific Reports, 2017)
Abstract Salamanders have developed a wide variety of antipredator mechanisms, including tail autotomy, colour patterns, and noxious skin secretions. As an addition to these tactics, the red-legged salamander (Plethodon shermani) uses adhesive secretions as part of its defensive strategy. The high bonding strength, the fast-curing nature, and the composition of the biobased materials makes salamander adhesives interesting for practical applications in the medical sector. To understand the adhesive secretions of P. shermani, its components were chemically analysed by energy dispersive X-ray spectroscopy (EDX), inductively coupled plasma mass spectrometry (ICP-MS), amino acid analysis, and spectroscopy (ATR-IR, Raman). In addition, proteins were separated by gel-electrophoresis and selected spots were characterised by peptide mass fingerprinting. The salamander secretion contains a high amount of water and predominantly proteins (around 77% in the dry stage). The gel-electrophoresis and peptide mass fingerprint analyses revealed a de novo set of peptides/proteins, largely with a pI between 5.0 and 8.0 and a molecular mass distribution between 10 and 170 kDa. Only low homologies with other proteins present in known databases could be identified. The results indicate that the secretions of the salamander Plethodon clearly differ chemically from those shown for other glue-producing terrestrial or marine species and thus represent a unique glue system.